8.4k views
0 votes
2(x - 4) = 7 - 3xwhat is the answer

1 Answer

3 votes

In order to find the value of x in this equation, first we need to expand the product in the left side:


2x-8=7-3x

Then, we isolate all terms with the variable in one side of the equation:


\begin{gathered} 2x+3x=7+8 \\ 5x=15 \end{gathered}

Finally, we divide both sides by the number multiplying the variable:


\begin{gathered} (5x)/(5)=(15)/(5) \\ x=3 \end{gathered}

So we have that x = 3

User Alpedar
by
4.4k points